The Conceptual Model of Digital Technologies Application in Supporting the Accounting Profession: Industrial Revolution 4.0 Era - Luluk Muhimatul IFADA; Sri SULISTYOWATI; Yunita AWANG; Azuraidah TAIB; Shazalina Mohamed SHUHIDAN; Zaiza Norsuriati Zainal ZAKARIA (Communications of International Proceedings, 2021)
This study examines the accounting profession that cannot be replaced by technology. As industry 4.0 develops, it raises concerns that the accounting profession will end in the digital era. Accountants must prepare more maturely to face their main competitors, namely technology and programmers. This study aims to identify the role of technology as a supporter of the accounting profession by examining the influence of digital technology and the impact of the industrial revolution 4.0 on the accounting profession. Additionally, this study observes the role of management accountants in moderating the relationship of digital technology and the impact of the industrial revolution 4.0 on the accounting profession. This study used an exploratory quantitative approach. The population of this study involved accounting students and accounting educators from public and private universities in Central Java, Indonesia. The method used is the non-probability sampling method based on specific criteria with regression analysis techniques. This research is expected to increase competence due to technological complexity so that the accounting profession can successfully meet future challenges.
Keywords: Industrial Revolution 4.0; Accounting Profession; Digital Technology; Management Accountant